10.1016/s1558-0164(06)70355-8 (CrossRef Listing of Deleted DOIs, 2000)
Background University-based dental clinics play an essential dual role by providing clinical training to future dentists while delivering accessible oral health services, particularly in settings with persistent socioeconomic disparities. Despite their importance, limited evidence describes longitudinal procedural patterns and clinical workload in adult care within Latin American predoctoral programs. This study examined the volume and trends of dental procedures provided to adult patients in predoctoral teaching clinics from 2019 to 2024. Methods A retrospective analysis of electronic clinical records was conducted, including all approved clinical procedures performed on adult patients (≥ 18 years) in fifth- and sixth-year predoctoral clinics. Procedures were grouped by clinical area for descriptive analyses and further aggregated into five treatment categories for trend analyses. Annual frequencies, distributions, the 10 most common procedures, and indicators of procedural workload per approved student were calculated. The impact of the COVID-19 pandemic on clinical production was also assessed. Results A total of 42,159 clinical procedures were recorded. Restorative dentistry accounted for the largest proportion (50.5%), followed by oral surgery/exodontics (33.6%). The 10 most frequent procedures accounted for more than half of all activity, led by resin restorations (18.1%), and simple extractions (15.0%). Procedural volume declined sharply in 2020 (1.2% of all procedures) but exceeded pre-pandemic levels by 2023-2024. Students completed an average of approximately 35-50 procedures per year, with the highest workload observed in surgical disciplines and lower procedural volumes in periodontics and endodontics. Conclusions Adult care in predoctoral teaching clinics was dominated by restorative and surgical procedures, reflecting population-level oral health needs and providing substantial exposure to common clinical conditions. However, comparatively lower procedural volumes in periodontal, endodontic, and complex prosthodontic care highlight opportunities to strengthen curricular balance, optimize case allocation, and leverage electronic clinical records to support evidence-based educational planning and equitable clinical training.